Biomimetics: Nature Helps: Toward Bioinspired Bactericidal Nanopatterns (Adv. Mater. Interfaces 16/2019). Issue 16 (23rd August 2019) - Ganjian, Mahya; Modaresifar, Khashayar; Ligeon, Manon R. O.; Kunkels, Lorenzo B.; Tümer, Nazli; Angeloni, Livia; Hagen, Cornelis W.; Otten, Linda G.; Hagedoorn, Peter‐Leon; Apachitei, Iulian; Fratila‐Apachitei, Lidy E.; Zadpoor, Amir A.
Abstract : Gram‐positive Staphylococcus aureus and Gram‐negative Escherichia coli bacterial cells are killed upon contact with surface nanopatterns with precisely controlled dimensions and arrangement, produced by electron beam‐induced deposition (EBID) technique. The main cause of such bactericidal effect is the cell wall being stretched and mechanically ruptured as the bacteria contact the nanopatterns. Further details can be found in article number1900640 by Mahya Ganjian, Khashayar Modaresifar, and co‐workers.